A glycosyl transferase family 43 protein involved in xylan biosynthesis is associated with straw digestibility in Brachypodium distachyon. Issue 3 (25th March 2018) - Whitehead, Caragh; Ostos Garrido, Francisco J.; Reymond, Matthieu; Simister, Rachael; Distelfeld, Assaf; Atienza, Sergio G.; Piston, Fernando; Gomez, Leonardo D.; McQueen‐Mason, Simon J.
Summary: The recalcitrance of secondary plant cell walls to digestion constrains biomass use for the production of sustainable bioproducts and for animal feed. We screened a population of Brachypodium recombinant inbred lines (RILs) for cell wall digestibility using commercial cellulases and detected a quantitative trait locus (QTL) associated with this trait. Examination of the chromosomal region associated with this QTL revealed a candidate gene that encodes a putative glycosyl transferase family (GT) 43 protein, orthologue of IRX14 in Arabidopsis, and hence predicted to be involved in the biosynthesis of xylan. Arabinoxylans form the major matrix polysaccharides in cell walls of grasses, such as Brachypodium. The parental lines of the RIL population carry alternative nonsynonymous polymorphisms in the Bd GT43A gene, which were inherited in the RIL progeny in a manner compatible with a causative role in the variation in straw digestibility. In order to validate the implied role of our candidate gene in affecting straw digestibility, we used RNA interference to lower the expression levels of the Bd GT43A gene in Brachypodium. The biomass of the silenced lines showed higher digestibility supporting a causative role of the Bd GT43A gene, suggesting that it might form a good target for improving straw digestibility in crops.